Taman Ecobric TK Dharma Wanita Desa Centong Kecamatan Gondang Kabupaten Mojokerto - Arika Fatmawati Ningrum; Shandy Pieter Pelamonia; Cintya Wulandari Sukirno Putri (Kanigara, 2022)
Making a garden needs to be done by everyone, there are many benefits to making a garden or planting trees, from cleaning the air to relieving stress. The existence of vacant land in Dharma Wanita Centong Kindergarten must be used to create a work program for making gardens with garden fences made of ecobric and planting ornamental flowers